Analisis Kepuasan Publik terhadap Kualitas Pelayanan Fasilitas Taman Cadika Medan sebagai Ruang Terbuka Hijau Kota - Fitri Aulia; Florentina Sitompul; Gabriel Novansyah Sihite; Johanes Johanes; Johs Charlos Hutabalian; Muhammad Idris; Mutia Adeliana P; Nabilla Panjaitan; Marthin Okuli Sitompul (Jurnal EMT KITA, 2026)
Public satisfaction is an important non-financial indicator in measuring the effectiveness of public asset management by local governments. Cadika Park Medan, as one of the green open spaces (GOS) in Medan City, provides various public facilities aimed at increasing citizens’ comfort. However, several facility-related issues that potentially affect visitor satisfaction are still found. This study aims to analyze the effect of facility quality on public satisfaction at Cadika Park Medan. This study uses a quantitative approach with a survey method of 42 respondents who visited Cadika Park Medan. The sampling technique used accidental sampling. The research instrument was a Likert-scale questionnaire consisting of 15 statement items. Data were analyzed using validity tests, reliability tests, descriptive statistics, and multiple linear regression analysis with the assistance of the Statistical Package for the Social Sciences (SPSS 26). The results show that all statement items were declared valid with correlation coefficients ranging from 0.726 to 0.915 and reliable with a Cronbach’s Alpha value of 0.964. Regression analysis results indicate that facility quality simultaneously has a significant effect on public satisfaction with an F value of 10.507 and a significance level of 0.000. The coefficient of determination (R Square) of 0.845 indicates that 84.5% of public satisfaction is influenced by facility quality, while 15.5% is influenced by other factors outside the study. Partially, indicator P12 was the most dominant variable affecting visitor satisfaction with a regression coefficient of 0.721 and significance of 0.015. This study concludes that improving facility quality, particularly in the aspect of general comfort, should be a priority for the Medan City Government in enhancing public service quality and managing green open spaces.